Imatinib inhibits pericyte-fibroblast transition and inflammation and promotes axon regeneration by blocking the PDGF-BB/PDGFRβ pathway in spinal cord injury - Fei Yao; Yang Luo; Yan-Chang Liu; Yi-Hao Chen; Yi-Teng Li; Xu-Yang Hu; Xing-Yu You; Shui-Sheng Yu; Zi-Yu Li; Lei Chen; Da-Sheng Tian; Mei-Ge Zheng; et al. (BMC, 2022)
Abstract Background Fibrotic scar formation and inflammation are characteristic pathologies of spinal cord injury (SCI) in the injured core, which has been widely regarded as the main barrier to axonal regeneration resulting in permanent functional recovery failure. Pericytes were shown to be the main source of fibroblasts that form fibrotic scar. However, the mechanism of pericyte-fibroblast transition after SCI remains elusive. Methods Fibrotic scarring and microvessels were assessed using immunofluorescence staining after establishing a crush SCI model. To study the process of pericyte-fibroblast transition, we analyzed pericyte marker and fibroblast marker expression using immunofluorescence. The distribution and cellular origin of platelet-derived growth factor (PDGF)-BB were examined with immunofluorescence. Pericyte-fibroblast transition was detected with immunohistochemistry and Western blot assays after PDGF-BB knockdown and blocking PDGF-BB/PDGFRβ signaling in vitro. Intrathecal injection of imatinib was used to selectively inhibit PDGF-BB/PDGFRβ signaling. The Basso mouse scale score and footprint analysis were performed to assess functional recovery. Subsequently, axonal regeneration, fibrotic scarring, fibroblast population, proliferation and apoptosis of PDGFRβ+ cells, microvessel leakage, and the inflammatory response were assessed with immunofluorescence. Results PDGFRβ+ pericytes detached from the blood vessel wall and transitioned into fibroblasts to form fibrotic scar after SCI. PDGF-BB was mainly distributed in the periphery of the injured core, and microvascular endothelial cells were one of the sources of PDGF-BB in the acute phase. Microvascular endothelial cells induced pericyte-fibroblast transition through the PDGF-BB/PDGFRβ signaling pathway in vitro. Pharmacologically blocking the PDGF-BB/PDGFRβ pathway promoted motor function recovery and axonal regeneration and inhibited fibrotic scar formation. After fibrotic scar formation, blocking the PDGFRβ receptor inhibited proliferation and promoted apoptosis of PDGFRβ+ cells. Imatinib did not alter pericyte coverage on microvessels, while microvessel leakage and inflammation were significantly decreased after imatinib treatment. Conclusions We reveal that the crosstalk between microvascular endothelial cells and pericytes promotes pericyte-fibroblast transition through the PDGF-BB/PDGFRβ signaling pathway. Our finding suggests that blocking the PDGF-BB/PDGFRβ signaling pathway with imatinib contributes to functional recovery, fibrotic scarring, and inflammatory attenuation after SCI and provides a potential target for the treatment of SCI.